Progressive motility – a potential predictive parameter for semen fertilization capacity in bovines. Issue 1 (23rd December 2014) - Li, Y.; Kalo, D.; Zeron, Y.; Roth, Z.
Summary: We examined the association between progressive motility of spermatozoa and in vitro fertilization (IVF) competence of bovine ejaculates. Fresh semen was evaluated using a computerized sperm quality analyzer for bulls using progressive motility as the primary parameter. Ejaculates with high progressive motility (HPM; >81%) were compared with those with low progressive motility (LPM; <62%). Semen concentration and sperm velocity were lower ( P < 0.05) in HPM versus LPM ejaculates. Volume and motile sperm concentration did not differ between groups ( P > 0.05). Examination of sperm morphology revealed a higher proportion of spermatozoa with abnormal morphology ( P < 0.01) in LPM versus HPM ejaculates, the predominant abnormal feature being a bent tail ( P < 0.05). Sperm viability, acrosome integrity and DNA fragmentation did not differ between HPM and LPM samples. Mitochondrial membrane potential was higher ( P < 0.01) in HPM versus LPM semen. Zinc concentrations in the seminal plasma correlated with progressive motility (R 2 = 0.463, P = 0.03). In addition, representative ejaculates from HPM and LPM groups were cryopreserved in straws and used for IVF. The proportions of embryos cleaved to 2- and 4-cell stages (88.1 ± 1.1 versus 80.5 ± 1.7, P = 0.001) and developed to blastocysts (33.5 ± 1.6 versus 23.5 ± 2.2, P = 0.026) were higher for HPM than LPM semen. The total cell number of embryos and blastocyst apoptotic index did not differ between groups. Although sperm progressive motility is associated with IVF competence, further examination is required to determine whether progressive motility can serve as a predictor of semen fertilization capacity in vivo .